Comparison of genomic prediction methods for residual feed intake in broilers. (15th March 2022) - He, Zhengxiao; Li, Sen; Li, Wei; Ding, Jiqiang; Zheng, Maiqing; Li, Qinghe; Fahey, Alan G.; Wen, Jie; Liu, Ranran; Zhao, Guiping
Summary: Residual feed intake (RFI) is a measure of the feed efficiency of animals. Previous studies have identified SNPs associated with RFI. The objective of this study was to compare the GBLUP model with the GA‐BLUP model including previously identified associated SNPs. The nine associated SNPs were obtained from the genome‐wide association study on a discovery population as preselection information. These models were analysed using ASREML software using a 5‐fold cross‐validation method on a validation population. With the genetic architecture (GA) matrix used, which was conducted with the nine RFI‐associated SNPs, the prediction accuracy of RFI was improved compared with the original GBLUP model. The calculated optimal ω was 0.981 for RFI, which is in line with the optimal range from 0.9 to 1.0 in the gradient test. The prediction accuracy increased by 2% in the GA‐BLUP model with ω being 0.981 compared with the GBLUP model. In conclusion, the GA‐BLUP with the nine RFI‐associated SNPs and an optimal ω can improve the prediction accuracy for a specific trait compared with GBLUP.